Love of Homeland Character Education through Green Harmony Program in State Elementary School Border Sambas - Malaysia - Mustapa Mustapa (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
This research aimed to know the character education of love of homeland through a green  harmony program at Border State Elementary School Sambas - Malaysia. Which viewed from the aspect of planning, implementation, and evaluation of learning characteristic of green harmony. Place of research conducted at Sajingan Besar 03 State Elementary School and Sasak 07 State Elementary School. This research was qualitative research that produces descriptive data. The subject of this research were headmasters, teachers, and students. Data collected by  interview, observation, and documentation. Data were analyzed using data analysis techniques with data collection steps, data reduction, data presentation, and data verification (drawing conclusions). Technique examination of data validity by using technique triangulation and source. The results showed that character education through green schools program implemented in the planning, implementation, and evaluation of  learning was running well. Characteristic learning planning begins with an understanding of school programs and planning of learning scenarios. The implementation of learning was carried out by applying SERU's learning (happy, effective, friendly, unique) and contextual learning approaches. Characteristic learning evaluation was conducted by observation, anacdetal record, and portfolio.